Chaos engineering with Docker. (Manning Publications, 2020)
The creator of the Kubernetes Chaos Engineering tool PowerfulSeal and the author of "Chaos Engineering", Mikolaj Pawlikowski, demonstrates how to apply chaos engineering to Docker to test its resilience.